Wild beasts : a gaijin female identity : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Creative Writing at Massey University, Manawatū, New Zealand EMBARGOED until 18 July 2027 - Knight, Athena (Massey University, 2025)
Ms Knight investigated representations of Western women's experiences in Japan through literary fiction written by gaijin (outsider) women. Her research demonstrated how these writers portray the complex welcome yet exclusion these women face in Japanese society. Her creative work, a novel-in-stories, presents narratives where such women find connection and belonging despite challenges.
Embargoed until 18 July 2027
Keywords: Lenihan, Colleen Maria. Kōhine; Kamata, Suzanne, 1965-. Losing Kei; Kamata, Suzanne, 1965-. The Baseball Widow; Ishii, Satoshi, 1936-2017; Women; Japan; Identity; Outsiders in literature; Cultural relations; Psychological aspects; Intercultural communication in literature; Feminism and literature; Other (Philosophy) in literature; Social life and customs; 360201 Creative writing (incl. scriptwriting)